Perancangan dan Implementasi Sistem Absensi Siswa Berbasis Web Menggunakan Face Recognition dan SMS Gateway - Firdaus, Ferdy Mohamad; Hidayat, Hidayat (Jurnal Manajemen Informatika JAMIKA, 2025)
This research aims to design and implement a student attendance system utilizing facial recognition technology and SMS gateway to increase the efficiency and accuracy of recording attendance in the Cimanggung Sumedang High School computer laboratory. The software development method used is the waterfall model. This method includes requirements analysis, system design, implementation, testing and maintenance. The system designed is web-based by utilizing the face-api.js API application to detect and recognize students' faces and the Twilio application as an SMS gateway to send attendance notifications to students' parents. The test results in this study show that the system can recognize one to seven students with good accuracy in one camera capture. In addition, this system successfully sends notifications to students' parents in real-time via SMS gateway when their children are not present at meetings in the computer laboratory. This research contributes to the development of a technology-based attendance system that can be implemented in an educational environment so that the attendance process can be carried out effectively and efficiently.